Deep Learning in Image Processing: Transforming Computer Vision - Sumithra M D (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Deep learning has been acclaimed to be the new sensation in image processing, improving the functionality of the computer vision system. The present work aims at testing the performance of deep models through image classification using Convolutional Neural Network (CNNs) and Transformer models. The experiments were conducted on the basis of versatile data set and the use of contrast photon restoration and adaptive histogram enhancement enhanced the result by 4-6 percent. The applied models were ResNet-50, EfficientNet-B0, and Vision Transformer(ViT) for which hyperparameter tuning and GPU-accelerated environments were applied for training. ViT attained the maximum classification accuracy of 92.5% hence out-performing the CNN based models. The statistical test also proved that there was significant difference (p < 0.05) in the performance. Maps of features and shaped specifications showed good hierarchical feature mapping and an AUC greater than 0.97 for ViT. Consequently, it can be seen that transformer-based models have significant benefits when applied to images. This work is beneficial to the enhancement of deep learning due to the fact that general model performance is investigated in relation to the influence of architectures as well as preprocessing methodologies.